Green calcium catalyst for biodiesel production: a review - Abdul Patar, Mohd Affifudin; Nasir, Nurul Fitriah; Osman, Shahrul Azmir (TRKU, 2020)
Biodiesel is one of the best choices for fuel alternatives. This is mainly due to its lower production value as it can easily be procured from cheap natural sources. It also has low emission of pollutant. However, some issues in regard to the production of biodiesel is that most production processes use homogeneous catalyst which is irretrievable and has expensive separation procedures. There is a method conducted to negates the outcomes stated above such as transesterification in supercritical conditions. But this method of transesterification also has its downside, high temperature and pressure processes indirectly will lead to higher cost and higher energy wastage. Therefore, presently, using heterogeneous catalyst are the way to go, especially catalyst derived from green resources. These types of catalyst are being extensively researched on due to its versatility, wide range of resources and promising results. Thus, this paper illustrates the compressive studies of biodiesel synthesis and assesses the latest achievement involved in heterogeneous catalyst derived from waste specifically waste from animal sources. Experimental data from great number of papers are reviewed thoroughly to provide an easier framework in producing biodiesel. Most importantly this review aims to diminish problems associated with heterogeneous catalyst while helping the industry to sustain the environment while still meeting energy demands.